IMAGING OF BINARY STARS IN THE PRESENCE OF DEFOCUSING - Hassan, Fouad (Iraqi Journal of Science, 2024)
In this paper a simulation for a mathematical two dimensional model was conductedto assess the presence of defocusing due to telescope aperture quality. The pointspread function (psf), Modulation transfer function (MTF), and Fourier frequenciesof binary star are computed in the absence and presence of defocusing. The resultsshow that the total frequency components of MTF decreases very sharply asdefocusing values goes to 6 and after this value the total frequency changes veryslightly afterward. The relative heights of the second to third peaks decrease rapidlyas defocusing values goes to 3 and slightly changes after that.